Severe Staphylococcus aureus infections in children: Case reports and management of positive Panton-Valentine leucocidin cases - Goemanne, Sophie; Tilmanne, Anne; Biarent, Dominique; Smeesters, Pierre; Simoni, Paolo; Mahadeb, Bhavna Ansuya; Vicinanza, Alfredo (Frontiers in Pediatrics, 2022)
Background : Staphylococcus aureus is a well-known bacterium associated with carriage and responsible for different types of infections. The Panton-Valentine Leucocidin (PVL) is a key virulence factor causing tissue necrosis. PVL can however be present in both benign and life-threatening infections. Case reports and management : We present 3 pediatric severe infections occurring over a period of only three weeks, in February 2021, and caused by genetically unrelated methicillin-sensible Staphylococcus aureus producing PVL in a tertiary children hospital in Belgium. The first one presented with a necrotizing pneumonia, the second one with a neck abscess extended to the mediastinum and the last one had a sacral osteomyelitis complicated by endocarditis. The management of these infections is mostly based on expert opinions. The most appropriate treatment seems to be the combination of early surgical drainage of infected collections with antibiotic regimen associating two antibiotics; beta-lactams and either clindamycin or linezolid. Human immunoglobulins also appear to be useful as adjunctive therapy. Conclusion : PVL-producing Staphylococcus aureus are associated with life-threatening infections in children. Prompt management is needed including surgery and appropriate antibiotic regimens.